Drivers of bank lending : new evidence from the crisis - Brinkmeyer, Hartmut (Schriften zum europäischen Management, 2015)
After the recent financial crisis has hooked the banking system to its very foundations, Hartmut Brinkmeyer contributes to the question of how bank characteristics influence bank loan supply during crisis periods by developing a well-founded theoretical framework. The econometrical design deploys a number of remarkably innovative ideas such as the implementation of a bank-specific, self-chosen target capital ratio or a very convincing approach to the disentanglement of loan supply and demand. The results of this study deliver a profound insight into the lending behavior of European banks and explicitly urge academic and practical discussion. Contents Monetary policy transmission A new view: Implications of financial innovation for the bank lending channel Bank lending against the background of the recent crisis Empirical analysis: Determinants of bank lending during normal and crisis periods  Target Groups Researchers and students dealing with monetary policy, banking and finance, banking management Decision makers in the fields of capital structure and treasury in banks  The Author Hartmut Brinkmeyer completed his doctoral thesis under the supervision of Prof. Dr. Christoph J. Börner and Prof. Dr. Ulrike Neyer at the Heinrich Heine University Düsseldorf. He studied Economics and Philosophy in Bayreuth, Rouen and Maastricht and works as a top management consultant. .